Blender cycles : materials and textures cookbook : over 40 practical recipes to create stunning materials and textures using the cycles rendering engine with blender /: materials and textures cookbook : over 40 practical recipes to create stunning materials and textures using the cycles rendering engine with blender. (2015) - Valenza, Enrico
No abstract available